Vinegar as an antimicrobial agent for control of Candida spp. in complete denture wearers - Pinto, Telma Maria Silva; Neves, Ana Christina Claro; Leão, Mariella Vieira Pereira; Jorge, Antonio Olavo Cardoso [UNESP] (FapUNIFESP (SciELO), 2008)
The use of denture is known to increase the carriage of Candida in healthy patients, and the proliferation of Candida albicans strains can be associated with denture-induced stomatitis. The aim of this study was to evaluate the use of vinegar as an antimicrobial agent for control of Candida spp. in complete upper denture wearers. Fifty-five patients were submitted to a detailed clinical interview and oral clinical examination, and were instructed to keep their dentures immersed in a 10% vinegar solution (pH less than 3) overnight for 45 days. Before and after the experimental period, saliva samples were collected for detection of Candida, counting of cfu/mL and identification of species by phenotypical tests (germ tube formation, chlamidoeonidia production, and carbohydrate fermentation and assimilation). The results were analyzed using Spearman's correlation and Student's t-test (p<0.05). Candida yeasts were present in 87.3% of saliva samples before the treatment. A significant reduction was verified in CFU/mL counts of Candida after treatment. A positive correlation between Candida and denture stomatitis was verified, since the decrease of cfu/mL counts was correlated with a reduction in cases of denture stomatitis. Although it was not able to eliminate C. albicans, the immersion of the complete denture in 10% vinegar solution, during the night, reduced the amounts (cfu/mL) of Cundida spp. in the saliva and the presence of denture stomatitis in the studied patients.
Keywords: Cundida albicuns; Cundidu; Denture; Vinegar